Conducta obstétrica a seguir en paciente con mola invasiva, manejo terapéutico. - Vargas Ponce, Angie Isabel (2023)
Invasive mole is a rare event characterized by excessive trophoblastic proliferation and infiltration of the trophoblast into the myometrium but shows no propensity for metastatic spread. We present a clinical case of a 48-year-old patient who came to the emergency area of General Hospital Babahoyo with symptoms of abdominal pain, transvaginal bleeding, nausea, and dizziness. The suspicion of a molar pregnancy arose after the first ultrasound, which revealed indicative features. Additionally, an elevation in the beta fraction of human chorionic gonadotropin was detected. It was decided to prepare the patient for her first instrumental uterine curettage (LUI). Ten days later, the patient returned, and additional ultrasound and laboratory studies were performed. These results supported the need for a second LUI. During this procedure, the patient experienced persistent bleeding, leading to hemodynamic compromise, triggering an emergency protocol. Measures were taken, including the insertion of an intrauterine balloon and the Zea technique, along with the administration of blood products to stabilize her. Discussions with the family regarding the complications took place, and a panhysterectomy was suggested due to continuous bleeding. The family members comprehended the explanation of the patient's obstetric clinical conditions and proceeded to sign the informed consent form. The intervention was successfully performed in a timely manner, and the patient's life was saved. The samples obtained during the surgery were sent for pathological examination.